Implementation of the Use of Digital Marketing as a Strategy to Improve the Performance of MSMES Assisted by the Kadin City of Bandung with Technopreneurship Character - Sunardi Sembiring Brahmana; Sri Astuti Pratminingsih; Uce Karna Suganda; Gagan Sugandi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The pandemic has given tremendous pressure and blows on MSME actors. Traditional marketing strategies can no longer be expected. MSME actors need new ways and breakthroughs to deal with this situation. One of the technologies currently developing in the world of marketing is the use of digital technology in marketing, which is then known as digital marketing. This is the background behind this community service activity to train MSME actors in the city of Bandung to understand and implement digital marketing. The activity was carried out on July 14, 2022. The activity has been going well. This training needs to be followed up by providing assistance to further enhanced MSME actors’ capability in designing and implementing digital marketing in their businesses.